An Integrated Approach for Effective Evaluation of Training Courses (Global Journal of Management and Business Research, 2022)
It is imperative to evaluate the training courses for which various procedures are practiced. Training courses were largely conducted with a set of objectives determined through Training Need Analysis (TNA). Evaluation of training (EoT) courses is carried out to elucidate the achievement of training objectives and benefit of training to trainee#x2019;s organization. The paper proposes a holistic evaluation methodology to assess the efficacy of training courses. Apart from discussing the concepts and principles of the suggested EoT method a model is put forth for its effective implementation. Data generation, processing procedures, and applicability in assessing the training functions at different levels are elaborated. The study suggests applying various formative and summative assessment tools to ensure the full achievement of the training objectives. These include pre and post-training tests, intermittent tests and independent hands-on tests in the simulated work environment to facilitate the transfer of learning. A numerical Trainee#x2019;s feedback pattern is suggested for impartial evaluation of the entire training activity. An assessment package designed in MS Excel is proposed for accurate and impartial assessment. It has a few interlinked worksheets for entering the trainees#x2019; responses and obtaining the total score of all the trainees for the tests conducted. It also exhibits the gain in level of knowledge and skill and facilitates criteria-based assessment. This package can be applied to ensure the achievement of training objectives which in turn motivate trainees in enhancing their on-job performance.
Keywords: evaluation; return on investment; assessment; skill development; performance; validation; on-job